A study on employee retention strategies in an it industry - CHERUKUR, MR.RAM BABU; J, Ms. MINI (The journal of contemporary issues in business and government, 2020)
The main aim of this study is to determine the various retention strategies adopted in an IT industry and also to know its impact on employee’s satisfaction towards these retention strategies undertaken by them. Here the study involves a descriptive research method as research design and samples for the finding purpose were collected from 180 respondents along with the help of primary data. The research finding was analysed using tools like Frequency analysis, Mean analysis, Independent T-test, One way ANOVA analysis and Regression analysis. Regression analysis is used to identify the employee satisfaction rewards retention strategies in an IT industry. It is evident from the result that the majority of respondent employees are highly satisfied towards the growth and recognition strategies undertaken by IT companies.